Traveling Irishness in the Long Nineteenth Century
XV, 258 p. 5 illus.
Keywords: Exploring the effects of traveling, migration, and other forms of cultural contact, particularly within Europe, this edited collection explores the act of traveling and the representation of traveling by Irish men and women from diverse walks of life in the period between Grattan’s Parliament (1782) and World War I (1914). This was a period marked by an increasing physical and cultural mobility of Irish throughout Britain, Continental Europe, the Americas, and the Pacific. Travel was undertaken for a variety of reasons: during the Romantic period, the ‘Grand Tour’ and what is now sometimes referred to as medical tourism brought Irish artists and intellectuals to Europe, where cultural exchanges with other writers, artists, and thinkers inspired them to introduce novel ideas and cultural forms to their Irish audiences. Showing this impact of the nineteenth-century Irish across national borders and their engagement with global cultural and linguistic traditions, the volume will provide novel insights into the transcultural spheres of the arts, literature, politics, and translation in which they were active. .